Analisis Minat Dan Perilakumasyarakat Dalam Penggunaan E-Wallet Xyz Dengan UTAUT2 - Erika Melania; Dwi Mustika Kusumawardani; Dwi Januarita Kusuma (STMIK Budi Darma, 2022)
Current technological developments affect all activities that were initially carried out manually, now can be done instantly such as a non-cash financial payment system, namely fintech. Fintech is defined as an industry consisting of companies that use technology, to make financial system services more efficient. One of the uses of fintech is e-wallet. E-wallet is an electronic service for digital payments and many other types of transactions. One of the e-wallet in Indonesia is Xyz. According to the MobileBoku report, the Indonesian market has five main players with the highest transaction growth sequence in 2020. Xyz is at the lowest position compared to other e-wallets. This shows the low number of users to use Xyz. This study focuses on the factors that influence the interest and behavior of the Indonesian people in the use of the Xyz e-wallet with the Unified Theory of Acceptance and Use of Technology2 (UTAUT2) model. The UTAUT2 model is the result of further development of the UTAUT model. Based on the above background, the research was conducted using the UTAUT2 model to analyze the factors that influence the interest and behavior of the Indonesian people in using Xyz. The purpose of this study was to determine the factors that influence interest in the use of Xyz as a sustainable development effort for the agency. The testing technique used is SEM-PLS. In accordance with the existing tests, it is known the factors that influence the use of the Xyz e-wallet application, such as facilitating conditions, hedonic motivation, and habits